Pengaruh Review dan Affiliate Marketing terhadap Impulsive Buying Konsumen Tiktok - Russel Gibran (Fakultas Ekonomi Universitas Islam 45, 2024)
The purpose of this study is to examine and analyze the impact of reviews and affiliate marketing on impulsive buying behavior. A quantitative descriptive method was employed, with data collected through questionnaires distributed to TikTok consumers. The sampling technique used was non-probability purposive sampling, conducted at a single point in time based on consumers’ multiple shopping experiences on TikTok. The data were analyzed using IBM SPSS Version 21. The results indicate that both reviews and affiliate marketing have a positive and significant effect on impulsive buying behavior. The coefficient of determination (R²) was 0.870, indicating that reviews and affiliate marketing together explain 87% of the variance in TikTok consumers’ impulsive buying behavior, while the remaining 13% is influenced by other factors not examined in this study.